Paying Too Much? Borrower Sophistication and Overpayment in the U.S. Mortgage Market - BHUTTA, NEIL; FUSTER, ANDREAS; HIZMO, AUREL (Journal of Finance, 2026)
ABSTRACT Comparing mortgage rates that borrowers obtain to rates that lenders could offer for the same loan, we find that many homeowners significantly overpay for their mortgage, with overpayment varying across borrower types and with market interest rates. Survey data reveal that borrowers' mortgage knowledge and shopping behavior strongly correlate with the rates they secure. We also document substantial variation in how expensive and profitable lenders are, without any evidence that expensive loans are associated with a better borrower experience. Despite many lenders operating in the U.S. mortgage market, limited borrower sophistication may provide lenders with market power.